Epidemiology of Operative Hand Infections Presenting at the Emergency Care Services of Civil Hospital Karachi - Shaikh, Unza; Zulfiqar, Bushra; Ali Khan, Faisal Akhlaq; Sami, Waqas; Zahid, Zaara; Kumar, Suneel (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore demographics, causes, types, bacteriology and outcome of operative hand infections presenting to the Emergency Department of Civil Hospital, Karachi. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Plastic and Reconstructive Surgery, Dr. Ruth K.M. Pfau Civil Hospital, Karachi Pakistan, from Aug 2021 to Apr 2022. Methodology: Patients presenting in Emergency Room with hand infections were studied as per the inclusion criteria. Hand surgeries were performed under general, regional or local anesthesia. Patients were followed till their discharge from the hospital. Results: A total of 280 patients were studied with predominance of males 182(65%) and median age of 48 years. 189(67.5%) patients had injury in right hand. Among 280 patients, total hand injuries were 300 and the most affected site was dorsum 72(7%) while palm volar was the least affected site 5(1.8%). Eighteen (6.4%) patients had more than one site involved in hand injury. The most frequent infection was superficial abscess 85(30.4%) followed by felon 81(28.9%), deep abscess 68(24.3%), paronychia 34(12.1%), necrotizing fasciitis 18(6.4%), osteomyelitis 10(3.6%) and septic arthritis 3(1.1%). Out of 280 patients, 44(15.7%) did not show positive culture growth. Staphylococcus aureus was the most frequently detected pathogen 167(59.6%) whereas Group A Streptococcus was seen in a single case. Conclusion: Our study concluded that occupational hand injuries were common because of trauma. The most frequently occurring infections in our settings was superficial abscess and the commonest causative pathogen was Staphylococcus aureus.